PENGARUH RASIO LIKUIDITAS DAN RASIO RENTABILITAS MODAL SENDIRI TERHADAP KINERJA PERUSAHAAN - Magdalena, Annaria; Lestari, Lastrid Bilfa (LPPM Institut Bisnis dan Informatika Kesatuan, 2015)
The purpose of this study was to determine the condition of liquidity ratios and profitability of own capital on the performance of PT. Indocement Tunggal Prakasa Tbk, PT. Holcim Indonesia, Tbk and PT. Cement Indonesia, Tbk., As well as to determine the effect of variable liquidity ratfios and profitability of own capital on the performance of companies using correlation and linear regression analysis. Based on the results of research conducted it can be concluded that the ratio of liquidity and profitability of capital itself has a strong influence and a significant relationship to company performance. Keywords: Liquidity, profitability